2019
DOI: 10.1093/neuonc/noz088
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies susceptibility loci for primary central nervous system lymphoma at 6p25.3 and 3p22.1: a LOC Network study

Abstract: BackgroundPrimary central nervous system lymphoma (PCNSL) is a rare form of extra-nodal non-Hodgkin lymphoma. PCNSL is a distinct subtype of non-Hodgkin lymphoma, with over 95% of tumors belonging to the diffuse large B-cell lymphoma (DLBCL) group. We have conducted a genome-wide association study (GWAS) on immunocompetent patients to address the possibility that common genetic variants influence the risk of developing PCNSL.MethodsWe performed a meta-analysis of 2 new GWASs of PCNSL totaling 475 cases and 113… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Indeed, recent study by Karim Labreche et al. ( 42 ) found that germline variants influenced PCNSL outcomes, and inflammation-related markers (e.g., interleukin-10) are potential targets. The underlying mechanism is still unclear and needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent study by Karim Labreche et al. ( 42 ) found that germline variants influenced PCNSL outcomes, and inflammation-related markers (e.g., interleukin-10) are potential targets. The underlying mechanism is still unclear and needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that it is necessary to screen appropriate populations (high inflammation risk) for receiving anti-inflammatory treatment besides the differences in anti-inflammatory drugs use. Indeed, recent study by Karim Labreche et al (42) found that germline variants influenced PCNSL outcomes, and inflammation-related markers (e.g., interleukin-10) are potential targets. The underlying mechanism is still unclear and needs to be investigated further.…”
Section: Competing-risks Regression Analysis Based On Different Years At Diagnosismentioning
confidence: 99%
“…Recognized as mature post-germinal B cells (ABC subtype like), the central nervous system (CNS) DLBCL represents only ≤1% of all lymphomas and approximately 2% of all primary CNS tumors; furthermore, 95% of tumors have a comparative histology with systemic DLBCL [ 67 , 75 ]. Since the blood brain barrier impedes R-CHOP treatment, high dose methotrexate (HD-MTX, >3 g/m 2 ) based regimens are the gold standard for PCNSL patients resulting in a five year survival rate of 30% and high risk of clinical neurotoxicity specially in patients > 60 [ 68 , 76 ].…”
Section: Gwas In B-cell Nhlmentioning
confidence: 99%
“…This study found one variant at loci 6p25.3 (rs116446171; EXOC2; p = 1.95 × 10 −13 ) previously found to be associated with DLBCL risk, other at loci 3p22.1 (rs41289586, ANO10 , p = 2.17 × 10 −8 ) and one strongly associated at HLA allele (rs2395192; between HLA-DRA and HLA-DRB5; p = 1.81 × 10 −7 ). ANO10 is a calcium-activated chloride channel transmembrane protein that might be involved in the innate immune defense and indirect activation of the Ras/Raf/MEK/ERK signaling pathway which affects cell proliferation [ 67 , 69 , 75 , 77 ].…”
Section: Gwas In B-cell Nhlmentioning
confidence: 99%
“…The methodology has been employed for a multitude of CNS tumors in adults, but only for a small subset of pediatric brain tumors, and shared susceptibility across tumor types attributable to common variants has not been explored. GWAS on adults have uncovered several low-risk SNPs specific to certain tumor types [14][15][16][17][18]. However, the two published GWAS on brain tumors in children and young adults have only been suggestive of a potential medulloblastoma risk locus at 18p11.23 [19] and of partial overlap in glioma risk loci between different age groups [20].…”
Section: Introductionmentioning
confidence: 99%